Pertanggungjawaban Pidana Korporasi Dalam Kasus Pencemaran Lingkungan Akibat Dumping Limbah B3 - Ade Venny Darma Putri; Syahrin, Alvi; Affila (JEBE: Journal of Environment Behavior and Engineering, 2025)
The illegal dumping of B3 waste into the environment can cause serious negative impacts. However, in principle, the dumping of B3 waste is permitted as long as it complies with the established terms and procedures. In reality, there are still many cases of B3 waste dumping without permits, which may lead to criminal liability, both for corporations and individuals. This research focuses on the legal framework regulating B3 waste disposal in Indonesia, the forms of corporate criminal liability in environmental pollution cases caused by B3 waste dumping, and the application of such liability in court decisions. The study applies normative juridical research methods using secondary data, including primary, secondary, and tertiary legal materials. Data were collected through literature review techniques and analyzed qualitatively. The results show that the regulation of B3 waste dumping in Indonesia is governed by Law No. 32 of 2009, Law No. 6 of 2023, Government Regulation No. 22 of 2021, and Minister of Environment and Forestry Regulation No. 6 of 2021. The forms of corporate criminal liability are regulated in the 2023 Criminal Code, which allows for criminal sanctions to be imposed on corporations, their executives, or both. Furthermore, Article 116 of the Environmental Protection and Management Law and Supreme Court Regulation No. 1 of 2023 also regulate corporate criminal liability in environmental cases. The application of corporate criminal liability to PT Synergy Oil Nusantara in Batam District Court Decision No. 491/Pid.Sus/2023/PN Btm was found to contain legal errors. However, the application of criminal liability to PT Datonglightway International Technology in Serang District Court Decision Number 89/Pid.Sus/2024/PN Srg was appropriate.